Divergent scaling of respiration rates to nitrogen and phosphorus across four woody seedlings between different growing seasons. Issue 21 (18th September 2017) - Fan, Ruirui; Sun, Jun; Yang, Fuchun; Li, Man; Zheng, Yuan; Zhong, Quanlin; Cheng, Dongliang
Abstract: Empirical studies indicate that the exponents governing the scaling of plant respiration rates ( R ) with respect to biomass ( M ) numerically vary between three‐fourth for adult plants and 1.0 for seedlings and saplings and are affected by nitrogen (N) and phosphorus (P) content. However, whether the scaling of R with respect to M (or N and P) varies among different phylogenetic groups (e.g., gymnosperms vs. angiosperms) or during the growing and dormant seasons remains unclear. We measured the whole‐plant R and M, and N and P content of the seedlings of four woody species during the growing season (early October) and the dormant season (January). The data show that (i) the scaling exponents of R versus M, R versus N, and R versus P differed significantly among the four species, but (ii), not between the growing and dormant seasons for each of the four species, although (iii) the normalization constants governing the scaling relationships were numerically greater for the growing season compared to the dormant season. In addition, (iv) the scaling exponents of R versus M, R versus N, and R versus P were numerically larger for the two angiosperm species compared to those of the two gymnosperm species, (v) the interspecific scaling exponents for the four species were greater during the growing season than in the dormant season, and (vi), interspecifically, P scaled nearly isometric with N content. Those findings indicate that the metabolic scaling relationships among R, M, N, and P manifest seasonal variation and differ between angiosperm and gymnosperm species, that is, there is no single, canonical scaling exponent for the seedlings of woody species. Abstract : Divergent scaling of respiration rates to nitrogen and phosphorus across four woody seedlings between different growing seasons.